Intellectual capital, R&D and sustainable financial performance: Moderating role of firm characteristics in an emerging market - Le, Hanh Thi My; Uyen, Nguyen Ngoc; Huong, Nguyen Thi Thanh; Ting, Irene Wei Kiong (Universiti Malaysia Sarawak, 2025)
Intellectual capital (IC) is a crucial driver of sustainable financial performance, particularly in the chemical and pharmaceutical industries. This study uses panel data from Vietnamese firms between 2017 and 2022 to investigate how IC and research and development (R&D) investment influence firm sustainability in an emerging market. This research, compared with previous studies, confirms the positive impact of IC and R&D on short- and long-term financial stability and also highlights the moderating role of firm characteristics. Specifically, firm size and growth rate enhance the benefits of R&D investment, whilst older firms exhibit a diminishing effect, potentially owing to reduced adaptability or innovation capacity. By emphasising the relationship amongst R&D, IC and firm characteristics, this study offers fresh insights into maximising financial sustainability in dynamic markets. Findings provide a foundation for future research and practical strategies to foster long-term competitiveness in emerging economies.